Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages MATERNAL MORTALITY Report of Meeting held at Friends' House, Euston Road, on November 15, 1932 PRICE ONE SHILLING (Including Postage) Printed by the LONDON CALEDONIAN PRESS LTD., 74 Swinton Street, Gray's Inn Road, W.C.1, and Published by THE MATERNAL MORTALITY COMMITTEE, 13 Chester Terrace, S.W.1 292/824/1/45